Influence of EBR on the structural resistance of RC slabs under quasi-static and blast loading: Experimental testing and numerical analysis. (1st December 2022) - Mourão, R.; Caçoilo, A.; Teixeira-Dias, F.; Maazoun, A.; Stratford, T.; Lecompte, D.
Abstract: Flexural strengthening of reinforced concrete (RC) structures with externally bonded reinforcement (EBR) using carbon fibre-reinforced polymers (CFRP) has in recent years received increased interest from specialists, particularly when dealing with protective structures against terrorist or accidental blast loading. Although a significant number of studies have been conducted on the failure modes of the bonded interface for quasi-static conditions, there is still limited published research on the effects of blast loading. In this paper, RC slabs externally strengthened with CFRP are tested in three-point bending as well as subjected to blast loading. The behaviour of the tested specimens under both loading regimes is evaluated with special focus on the mechanisms that lead to the disruption of the CFRP. It was found that the debonding of the CFRP was caused, in both cases, by the fracture and separation of a thin layer of concrete in the near vicinity of the bonded interface. However, the mechanisms that lead to this failure differ. A numerical model was developed and simulations performed using the finite element (FE) code LS-DYNA to investigate the validity of commonly used simplifications on the modelling of the interface in both cases. It was found that although the modelling technique used to represent the disruption of CFRP under quasi-static conditions provide accurate results, it does not return accurate predictions of the debonding of CFRP under blast loading. Highlights: The behaviour of RC beams externally strengthened with CFRP under quasi-static and blast loading is discussed. Although CFRP debonding is similar in both loading regimes, the mechanisms that lead to failure differ. The validity of commonly used simplifications on the modelling of the disruption of CFRP is analysed numerically. CFRP external reinforcement increased the maximum static displacement before failure and the maximum load capacity.